Answers

2016-04-20T16:05:53+05:30
R = rate of simple interest (no compound)
At the beginning: 12500
After 1 year:         12500 +  R × 12500 = 12500(1 + R)
After 2 years:       12500(1 +  R)  + R × 12500 = 12500(1 + 2R)
After 3 years:       12500 × (1 + 3R)
After 4 years:       12500 × (1 + 4R)
After n years:       12500 × (1 + nR)

12500 (1 + 4R) = 15500
1 + 4R = 15500 ÷ 12500
1 + 4R = 1.24
4R = 1.24 - 1
4R = 0.24
R = 0.06 = 6%


0
2016-04-20T16:27:32+05:30
Here,
p = 12500
t = 4
I = Interest amount = total amount - principle amont
  = 15500 - 12500
  = 3000
 let, rate of interest = r
p × t× r / 100 = 3000
⇒(12500 × 4 × r ) / 100 = 3000
⇒500 r = 3000
⇒ r = rate of interest = 3000/500 = 6 %

0
p × t × r / 100 is only to equal 15500 - 12500 = 3000, not 15500
but still , ur answer and my answer are different......why?
While (12500 × 4 × r) / 100 = 500r not 900r ;)
thanq .........i did a silly mistake